ENVIRONMENTAL MANAGEMENT STRATEGY ON RIVERBANKS AS EROSION PREVENTION (International Conference on Social and Islamic Studies, 2021)
Riverbanks have an important role in maintaining river ecosystems. Erosion and sedimentation as the dynamics of watersheds determine the sustainability of riverecosystem functions. This study describes environmental management strategieson riverbanks to prevent erosion. The research method is descriptive quantitative.The location is three districts in South Sulawesi as managers of the Jeneberang River, Walanane River, and Saddang River. The primary data sources were 27 experts consisting of 21 government officials and six experts from higher education. The SWOT analysis method uses aspects of Strengths, Weaknesses, Opportunities, and Threats to find the strategy. The data analysis results indicate the development of green belts on the riverbanks with local vegetation maintenance. Therefore, the right strategy for achieving environmental quality on river banks is improving the quality of vegetation on river banks by strengthening the role of village institutions. Developing an education program to increase community knowledge, attitudes, and skills in local plant conservation on river banks is very important in planting and maintaining vegetation.